Three asymmetric Salamo-type copper(II) and cobalt(II) complexes: Syntheses, structures and fluorescent properties. (17th February 2017) - Dong, Yin-Juan; Dong, Xiu-Yan; Dong, Wen-Kui; Zhang, Yang; Zhang, Li-Sha
Graphical abstract: Three new supermolecular complexes, [Cu(HL 1 )] (1 ), [Cu(L 2 )H2 O] (2 ) and [Co2 (L 2 )2 ]·3CH3 CN (3 ), have been synthesized and structurally characterized. These self-assembling complexes form different dimensional supramolecular structures through intermolecular and intramolecular hydrogen bonds. Meanwhile, the fluorescence behavior of the two Cu(II) complexes in DMF is discussed. Abstract: Three new supramolecular complexes, [Cu(HL 1 )] (1 ), [Cu(L 2 )H2 O] (2 ) and [Co2 (L 2 )2 ]·3CH3 CN (3 ), were designed and synthesized by the reaction of 5-hydroxy-4′, 6′-dibromo-2, 2′-[ethylenediyldioxybis(nitrilomethylidyne)]diphenol (H3 L 1 ) with Cu(II) acetate hydrate (for1 ); and 6-methoxy-4′, 6′-dibromo-2, 2′-[ethylenediyldioxybis(nitrilomethylidyne)]diphenol (H2 L 2 ) with Cu(II) acetate hydrate (for2 ) and cobalt(II) acetate tetrahydrate (for3 ), respectively, and were characterized by element analyses, X-ray crystallography, FT-IR, UV–Vis and fluorescence spectra. Complex1 is mononuclear and tetra-coordinated and adopts a distorted square-planar geometry, likewise, complex2 is mononuclear and penta-coordinated with a square-pyramidal geometry, however, complex3 is dinuclear with the two Co(II) atoms having the same coordination environments and adopt a trigonal bipyramidal geometry. These self-assembling complexes form different dimensional supramolecular structures through inter- and intramolecular hydrogen bonds. Meanwhile, photophysical properties of the three complexes have also been discussed. Furthermore, the fluorescence behaviors of the two Cu(II) complexes in DMF are discussed.